Physicochemical properties of alkali-treated new cellulosic fiber from cotton shell. Issue 4 (18th May 2016) - Rajkumar, R.; Manikandan, A.; Saravanakumar, S. S.
ABSTRACT: The aim of this present investigation was to identify a new natural fiber from one of the cotton plant's byproducts, which is chemically modified by alkaline treatment. Its characteristics were examined for the preparation of natural fiber–reinforced polymer composites. The cotton shell fibers (CSFs) were extracted from the cotton shell and its degree of crystallinity, crystallite size, chemical constituents group, and thermal stability were determined by X-ray diffraction, Fourier transform infrared (FTIR) spectroscopy and thermogravimetric analysis. The alkali treatment of CSFs is optimized at 5% (w/v) NaOH aqueous solution with 45 min soaking time.